Sustainable Performance Model and Strategy: A Conceptual Framework - Arifin, Firmansyah; Wiryono, Sudarso Kaderi; Damayanti, Sylviana Maya; Yudoko, Gatot (Research Synergy Foundation, 2023)
This study is driven by the conditions of the energy sector, particularly the